2021
DOI: 10.12973/eu-jer.10.4.2105
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Evaluation of Game as a Didactic Resource in the Communication of Teachers Through Social Networks

Abstract: <p style="text-align: justify;">This research presents an analysis of the value given to the game as an educational resource on social networks. The purpose of this study is to analyze the discourse on Twitter of the different educational agents (teachers and other educational professionals) to know the value given to the use of this tool and how the social network is an educational form of communication and interaction. From a qualitative methodology, a descriptive-interpretative study of the informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Therefore, teachers' motivational and emotional orientations (value, self-efficacy, and anxiety) are important for successful professional self-realisation. Higueras-Rodríguez et al [41] paid attention to the educational value of social networks, specifically for Twitter, and found that the main values include gamification and interactivity. Kucirkova et al [42] reached values through the study of personalisation of the educational environment in a broad sense.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, teachers' motivational and emotional orientations (value, self-efficacy, and anxiety) are important for successful professional self-realisation. Higueras-Rodríguez et al [41] paid attention to the educational value of social networks, specifically for Twitter, and found that the main values include gamification and interactivity. Kucirkova et al [42] reached values through the study of personalisation of the educational environment in a broad sense.…”
Section: Discussionmentioning
confidence: 99%